Transcription factor SlbZIP12 affects tomato shelf life by mediating the ethylene biosynthesis at postharvest stage - Abdul Karim Amin; Wenyi Zhu; Pengwei Li; Shi Shi; Mengru Qin; Yan He; Huizhen Zhang; Hong Yao; Shuqi Chen; Hamza Latif; Mohammad Yousof Soltani; Mahmood Hemat; et al. (Postharvest Biology and Technology, 2026)

Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

The convergent threat of ESBL, carbapenemase, and MCR resistance determinants in the Hong Kong food chain: A cross-sectional surveillance study - Wing Ho Li; Tsz Tuen Li; Jordan Yik Hei Fong; Ruheng Chen; Pacy Yin Mei Leung; Elaine Chan; Xueyan Liu; Winnie Wing Yi Tai; Zera Kin Yee Leung; Hwei Huih Lee; Wai-Man Tong; Yan Zhao; et al. (International Journal of Food Microbiology, 2026)

Characterization and antibacterial activity of a Bacteriocin-like Inhibitory Substance (BLIS) produced by Levilactobacillus brevis - Jiayue Wang; Xinyu Wang; Yuhang Zheng; Lirong Yang; Rongjie Chen; Man Yan; Wanli Sha; Baishuang Yin; Wenlong Dong (Brazilian Journal of Microbiology, 2026)

Dnmt3a-mediated abnormal DNA methylation is associated with myelination deficits in offspring of advanced maternal age rats - Chunxue Jiang; Xinru Yan; Man Xu; Li Cheng; Li Jiang; Wei Han (Molecular Biology Reports, 2026)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Intelligent integration in agricultural insect management equipment: applications, challenges, and future directions - Bowen Lv; Yan Huo; Wenyong Li; Yuxin Wang; Huiting Wang; Jingyu Chen; Ruicheng Qiu; Zhao Zhang; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2026)

Tidal groundwater flow drives dissolved nitrogen cycling: linking internal transformation to interfacial flux - Ao Li; Yan Zhang; Zhenyang Li; Man Zhao; Jingjing Lyu; Lingwei Xu; Zhenyan Wang; Hailong Li; Guangxuan Han; Kai Xiao (Journal of Hydrology, 2026)

Reconstituted soybean protein isolate emulsion gel induced by transglutaminase: structure, stability, and application in quercetin delivery - Jiannan Yan; Fangxiao Xing; Pan Liu; Xiuying Xu; Libin Feng; Hongyang Man; Chengbin Zhao; Hao Zhang; Jianjiang Wei; Jingsheng Liu (Food Chemistry, 2026)

Towards sustainable multi-bed hospital wards: numerical evaluation of infection control, thermal comfort, and energy savings under real-world ventilation strategies - Mei Yan Chong; Hui An; Brenda Sze Peng Ang; Chew Beng Soh; Szu-Cheng Chien; Peng Cheng Wang; Simon Ching Man Yu (Energy and Buildings, 2026)

Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Allelic variation in cis-regulation of UNE12 underlies differential Verticillium wilt resistance in tetraploid cottons - Meixia Xie; Ziming Li; Jiaxuan Zhao; Minghui Ye; Mengjia Jiao; Zhicheng Wang; Xinxin Zheng; Xinyu Zhang; Jin Zhang; Yan Wang; Man Gu; Lingxia Zhai; et al. (Science Bulletin, 2026)

A phased immune cascade in the silver pomfret spleen: from antigen processing to cytotoxic activation during Photobacterium damselae subsp. damselae infection - Yuanbo Li; Denggui Chen; Xiang Chen; Zhixuan Lu; Man Zhang; Youyi Zhang; Jiabao Hu; Yajun Wang; Xiaojun Yan (Aquaculture, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Manipulating the organic-salt selectivity of N-2-hydroxyethylpiperazine based poly-ester-amide (PEA) membranes for antibiotic-NaCl separation - Qinghua Guo; Tao Shi; Lu Dai; Zhiguo Yan; Qun Chen; Man Xu; Yanbo Li (Desalination, 2026)

Lactococcus cremoris subsp. sagaensis subsp. nov., Isolated from Naturally Fermented Yogurt - Lin Cheng; Tian-Xue Wang; Chun Yan Li; Chaoxin Man; Chun Tao Gu (Current Microbiology, 2026)

An LLM-based framework to evaluate the suitability and accessibility of campsites: A case study of Changsha, China - Yu Man; Yan Shi; Ying Zeng; Minghui Li; Jingsha Han (Sustainable Cities and Society, 2026)

Hydrological response to glacier peak water in the largest inland river basin of China - Haodong Lyu; Gonghuan Fang; Yaning Chen; Wenting Liang; Lei Wang; Jianmin Qiao; Man Chen; Xiaolong Yan; Ruoyan Li; Shiru Han (Journal of Hydrology, 2026)

F–53B exacerbates doxorubicin-induced cardiotoxicity by impairing NRF2-dependent ferroptosis defense - Chaobo Yang; Jingbin Guo; Man Long; Haojing Liu; Jiewen Cai; Rongxin Zhang; Zhi Zeng; Yan Zhu; Haiqiong Liu (Chemico-Biological Interactions, 2026)

Cellular Responses to Cold Stress in Pampus argenteus: Involvement of Dusp5 in MAPK Signaling, Apoptosis Suppression, and Organelle Protection - Mengke Tang; Man Zhang; Yubei Qiu; Yuanbo Li; Qinqin Dai; Xianglong Chen; Chongyang Wang; Fangjun Xu; Lu Zhang; Zi Yuan; Xiaojun Yan; Jiabao Hu; et al. (Marine Biotechnology, 2026)

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Homothorax regulates BarH1 expression and olfactory perception in Monochamus alternatus hope - Qi-Cheng Li; Sheng-Xin Wu; Mei-Jiao Yang; Pu-Yuan Zhang; Yan-Ling Wei; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Nitrogen-Phosphorus Co-Doped Biochar for Persulfate Activation in Sulfadiazine Degradation: Degradation Performance, Mechanism and Toxicity Assessment - Weiwei Yu; Rongqi Liu; Ting Ai; Yufeng Mao; Jiajie Li; Lu Lv; Dan Liu; Yan Luo; Wang Xin; Man Luo; Boyu Liu (Water, Air, & Soil Pollution, 2026)

Palaeowildfire regimes and their palaeoenvironmental significance during the Middle Jurassic of the Ordos Basin - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Man Huang; Langlang Wang; Xiaotao Xu; Xiaoyun Yan; Jing Lu (Science China Earth Sciences, 2026)

Potential mechanism of Lactiflorin in treating ulcerative colitis via modulation of the PI3K/AKT pathway: a study integrating network analysis, bioinformatics analysis, and experimental evidence - Mengjia Zhang; Haotian Li; Ningjuan Yan; Man Meng; Xiaolan Su; Yanjun Liu; Runhua Chen; Jianqin Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The combined effects of sulfamethoxazole and ammonia in manure-based biomethanation process: Reactor performances, microbial responses, and metabolic mechanisms - Mingyao Zhou; Shuaishuai Man; Fei Shen; Mohamed Hemida Abd-Alla; Han Wang; Qun Yan (Journal of Environmental Chemical Engineering, 2026)

Global evidence on vitamins in human milk: A 2002–2022 systematic review with a focus on China and implications for maternal diet and infant formula - Yan Yang; Xinggang Ni; Nian Liu; Quanzhang Li; Qi Fang; Ignatius Man-Yau Szeto; Sufang Duan; Teng Wei; Tianyu Rao; Zeyuan Deng; Ting Li; Jing Li (Food Research International, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Biogenic FeS Reshapes microbial interactions to regulate acetogenesis in CO2-Fed microbial electrosynthesis - Huixing Wu; Han Wang; Shuaishuai Man; Qun Yan (Bioresource Technology, 2026)

Physical mixing buffers heatwave-induced suppression of phytoplankton growth: evidence from a mesocosm experiment - Man Xiao; Surui Zhang; Jing Lu; Enjun Liu; Jianming Deng; Zhenhua Yan; Guangwei Zhu (Aquatic Ecology, 2026)

Health risks of exposure to organotin compounds via seafood consumption after their legal ban - Yan Jiang; Man Sze Kwok; Mengyang Liu; Kenneth M.Y. Leung (Marine Pollution Bulletin, 2026)

Red Sea bream iridovirus (RSIV) infection elicits cell death modes—Apoptosis and ferroptosis in silver Pomfret (Pampus argenteus) - Yuanbo Li; Youyi Zhang; Wuqiang Xia; Ting Chen; Zukang Feng; Denggui Chen; Fangjun Xu; Man Zhang; Yajun Wang; Xiaojun Yan; Jiabao Hu (Aquaculture, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Synthesis of ZIF-8 derived porous carbon via morphology-controlled electrodeposited ZnO thin films for in-plane micro-supercapacitors - Jun-Yan Lin; Ramasamy Velmurugan; Jing-Jie Lin; Zhi-Ting Huang; Man-Ning Lu; Martin Hulman; Chien-Kuo Hsieh; Jeng-Yu Lin (Chemical Engineering Journal, 2026)

Structural evolution-based ancestral sequence reconstruction of medium-chain alcohol dehydrogenase for efficient synthesis of fused-ring chiral alcohols - Jun Wang; Songyin Zhao; Lehang Li; Manman Zhu; Man Zou; Xin Su; Jie Gu; Yan Xu; Yao Nie (Bioresource Technology, 2026)

Experimental and numerical study of a novel thermochromic bifacial photovoltaic glazing system - Chuyao Wang; Man Yi Wong; Hao Zhou; Zhe Song; Kaixin Lin; Hongxing Yang; Jie Ji; Chi Yan Tso (Building and Environment, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Biochemical insights into the alleviated inhibition on nitrogen metabolism by micro-and nano-plastics at the biocathode of bioelectrochemical systems - Jiamin Su; Han Wang; Shuaishuai Man; Qun Yan (Bioresource Technology, 2026)

Electro-biochemical profiles of the boosted CO2-to-acetate conversion in microbial electrosynthesis using FeS-Hydrochar modified cathodes - Huixing Wu; Han Wang; Shuaishuai Man; Qun Yan (Bioresource Technology, 2026)

Modulation of Glutamate Release by Dexmedetomidine Preserves Dendritic Spines and Alleviates Cognitive Impairment in a Murine Model of Perioperative Neurocognitive Disorder - Yan Zhang; Junzhao Li; Xueju Wang; Zhongyu Zhang; Shuai Long; Chuanyu Edward Li; Yan Liu; John Man Tak Chu; Raymond Chuen-Chung Chang; Gordon Tin-Chun Wong; Yong Zhang (Neuroscience Bulletin, 2026)
Perioperative neurocognitive disorders (PNDs) represent a significant challenge in the perioperative setting, while the pathophysiology of PNDs remains unclear. Utilizing a murine model of abdominal surgery, we found that abnormal glutamatergic neurotransmission in the medial prefrontal cortex (mPFC) and hippocampus contributes to postoperative cognitive impairments. Increases in the frequency of miniature excitatory postsynaptic currents in both the mPFC and CA1 neurons indicate enhanced presynaptic glutamate release while having little effect on inhibitory neurotransmission. Surgery also enhances glutamate release from presynaptic terminals in the Schaffer collateral pathway. In addition, abdominal surgery increased the activation of microglia and astrocytes, elevated central inflammatory markers, and reduced excitatory amino-acid transporter-2 expression. Dexmedetomidine significantly mitigates the postoperative cognitive deficits by reducing inflammation and preserving neuronal structural complexity and dendritic spine stability, likely through inhibiting glutamate release and enhancing its reuptake. These findings advance our understanding of the etiology of PNDs and provide hints for potential intervention.

Spatial variability of the phosphorus forms and diffusive flux across the sediment–water interface: insights from a typical small watershed to the national scale - Zheng Yan; Jidong Zheng; Zhenyang Li; Jiahao Chen; Man Zhao; Jingjing Lv; Zhenyan Wang; Feng Pan; Kai Xiao (Journal of Hydrology, 2026)

Intensified wildfire activity due to volcanism across the Triassic-Jurassic boundary in northwestern China - Wenxin Hu; Qingyong Luo; Jianfa Chen; Linhao Fang; Man Lu; Medet Junussov; Tao Du; Xintong Liu; Xiaohang Pan; Gui Wang; Fangchao Yan (International Journal of Coal Geology, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Enhanced photocatalytic uranium(VI) removal via oxygen vacancy-assisted Z-scheme SPC-Bi/Bi2WO6 with plasmonic Bi activation - Le Tao; Xue-Qi Fan; Yi-Man Sun; Yue Hu; Wen-Yan Guo; De-Qiang Ji; Hong-Jun Wu; De-Bin Ji (Chemical Engineering Journal, 2026)

Electro-oxidation of tris (2-chloropropyl) phosphate (TCPP) employing Ti/TiO2 NTA/PbO2-La-CNT composite as anode: electrode preparation, characterization and process exploration - Haifan Dong; Shuaishuai Man; Han Wang; Qun Yan (Journal of Water Process Engineering, 2026)

From genes to products: High-efficiency biosynthesis and holistic optimization strategies for monounsaturated fatty acids - Lu-Wei Xu; Yan-Cheng Lin; Yi-Ting Shen; Xin Qi; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Microbiology, 2026)

Electrocatalytic upcycling of polyethylene terephthalate plastic wastes with hydrogen generation over tremella-like oxygen-deficient NiAl-LDHs microflowers - Yutong Zhang; Huiming Wen; Wanrong Bu; Bin Liu; Zhenhao Xu; Ke Li; Man Zhao; Xiongfei Huang; Yuchen Wang; Kai Yan (Chemical Engineering Journal, 2026)

The chemotaxonomic significance of chemical constituents from Gynostemma pentaphyllum - Hou-Lin Peng; Man-Hui Yang; Wu-Di Zhai; Wen-Juan Li; Jing Liu; Yan Zhang (Biochemical Systematics and Ecology, 2026)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Impacts of climate change and land use changes on heat island effect in the Guangdong-Hong Kong-Macao Greater Bay Area under the SSP-RCP framework - Xin Yan; Alex Hay-Man Ng; Xun Liu; Qianqian Zhou; Linlin Ge (Sustainable Cities and Society, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

Dermal bioaccessibility of organophosphate esters in indoor dust: Influencing factors, release kinetics, and health risk assessment - Zijia Hong; Yu Bon Man; Yue Li; Linying Xiao; Shitong Han; Zhuoyao Chen; Bingyan Lan; Xiaomin Yan; Jiwen Luo; Lixuan Zeng; Yuan Kang (Journal of Hazardous Materials, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

The effect and mechanism of sublethal injury by lactic acid on Salmonella Typhimurium planktonic and biofilm cells - Mengjiao Zhang; Yunshuang Man; Rongrong Yang; Yudi Wang; Dongling Yan; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Microbiology, 2025)

Lipid metabolism homeostasis and low-level glycogen metabolism in the Harderian gland of hibernating Daurian ground squirrels - Lu-Fan Li; Yu-Jing Yan; Yi-Man Liu; Qing-Ying Wang; Ming-Di Wang; Jin-Hui Xu; Zhe Wang (Cryobiology, 2025)

Dynamic sealing mechanisms of drilling fluid in fractured coalbed methane formations: a coupled CFD-DEM numerical study - Zichen Han; Xianyu Yang; Ni Ren; Jiwei Song; Meng Zhao; Man Xue; Mengjia Liang; Xinmin Yan; Chunzheng Jin; Guosheng Jiang; Jihua Cai (Computers and Geotechnics, 2025)

SnO2-decorated three-dimensional carbon nanotubes as aluminophilic skeleton for anode-less aluminum-ion batteries - Yuqing Gao; Chen Xie; Zekai Lv; Yibiao Guan; Wenjun Shen; Kang Yan; Xi Wang; Man Xie; Yuefeng Su; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Self-sacrificing strategy enables amorphous precursor mediated crystallization of phase-pure Na4Fe3(PO4)2P2O7 for advanced sodium-ion batteries - Yan Chen; Yixin Zhang; Yuefeng Su; Zekai Lv; Wei Wang; Sanchao Liu; Wenbin Sun; Meng Wang; Man Xie (Chemical Engineering Journal, 2025)

Magnetite modulates bacterial cooperation during cathodic nitrogen removal in bioelectrochemical systems under trace dissolved oxygen - Ziang Kong; Han Wang; Shuaishuai Man; Qun Yan (Bioresource Technology, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Cadmium-induced nucleus pulposus derived mesenchymal stem cells apoptosis via MAPK signaling pathway contributes to IVD degeneration - Man Hu; Yu Zhang; Wen-jie Zhao; Xin Liu; Yan-feng Zhang; Da-xu Liu; Xin-min Feng; Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2025)

3D Geomechanical Modeling for Sweet Spot Identification in Thin-Layer Carbonate Reservoirs - Jian Yang; Zhouyang Wang; Miao Yang; Yuanyu Yang; Xucheng Li; Le Luo; Yan Fu; Man Huang; Zhi Zhong; Dongchao Su; Zikun Li; Fulong Ning (Geotechnical and Geological Engineering, 2025)

The impact of urbanization on carbon emissions of rural households: a study based on micro-level measurement - Manman Gao; Man Wang; Huimin Cao; Zhenyu Yan; Jiapeng Xu (Clean Technologies and Environmental Policy, 2025)

Control of post-harvest soft rot (Rhizopus stolonifer) on sweet cherry using volatile organic compounds produced by Bacillus velezensis Q-84 - Jian-Yu Wang; Min-Xin Mao; Chun-Yan Xu; Man Zou; Wen-Ting Bao; Yi-Ning Zhou; Shun-Qing Hu; Ke-Xin Jiao; Qing-Kun Lu; Peng Zhao; Kun-Peng Zhang; Yi-Lun Chen; et al. (BioControl, 2025)

Discovery of milk-derived antimicrobial peptides in human milk by DeepMAMP based on peptidomics technology and deep learning method - Wenhao Yu; Xinchen Zhang; Yang Yu; Dengcai Zhao; Sufang Duan; Ignatius Man-Yau Szeto; Jian He; Li Liu; Yan Jin (Food Chemistry, 2025)

Comparative study on the structural, antioxidant and functional properties of hydrolysates from Pleurotus erynigii and Pleurotus ostreatus protein by alcalase and trypsin - Xiao-Xuan Hou; Shu-Jing Bing; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang; Hai-Zhen Mo (Food Bioscience, 2025)

Liposome-delivered natural antimicrobials in foods: Antibacterial efficacy and mechanisms - Dongling Yan; Yudi Wang; Rongrong Yang; Yunshuang Man; Hui Tang; Qianqian Yu; Lele Shao (Food Bioscience, 2025)

Whole-genome resequencing and transcriptomes analysis of hermaphroditism mechanisms in silver pomfret (Pampus argenteus): The role of feeding and lipid metabolism - Yaya Li; Jiabao Hu; Chongyang Wang; Shipan Zhao; Man Zhang; Youyi Zhang; Yuanbo Li; Qingqing Dai; Mengke Tang; Chunlai Qin; Zukang Feng; Shanliang Xu; et al. (Aquaculture, 2025)

Humic acid alters the surrounding-magnetite microecological environment for denitrifying communities under organic carbon limitation: From ecological to molecular scales - Ziang Kong; Bin Huang; Han Wang; Shuaishuai Man; Qun Yan (Chemical Engineering Journal, 2025)

Intestinal microbiota and metabolomics reveal the intestinal damage caused by imidacloprid in loaches (Misgurnus anguillicaudatus) - Yingbing Su; Yongxi Huang; Pupu Yan; Jiali Liu; Man Liu; Jun Zhu; Yinuo Gong; Haishan Chen; Liwei Guo (Aquatic Toxicology, 2025)

Spatiotemporal evolution and influencing factors of Resource-Environment pressure: a case of the new Western Land-Sea corridor in China - Yan Tang; Shan Gao; Yunpei Cheng; Man Xiao; Tian Hao; Xinzhi Wang (Environment, Development and Sustainability, 2025)

Enhanced East Asian summer monsoon circulation during the Early to Middle Bronze Age - Jiawei Jiang; Yancheng Zhang; Deming Kong; Hongxuan Lu; Huanye Wang; Yu Liang; Charlotte Wing Man Lee; Hongwei Liu; Bowen Meng; Zhouqing Xie; Hong Yan; Weiguo Liu; et al. (Quaternary Science Reviews, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

An AIE-activated fluorescent sensor for one-step concurrent detection and bioimaging of perfluorooctanoic acid and perfluorooctane sulfonate in vitro and in vivo - Penglai Yao; Jiale Ou; Dede Zhao; Shuping Zhou; Qi Wang; Yan Feng; Man Chen; Xiangming Meng (Journal of Hazardous Materials, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Degradation of microplastics by electrocoagulation technology: Combination oxidation and flocculation effects - Shuaishuai Man; Xinyu Liu; Volker Presser; Shaohan Dong; Ziyang Li; Liwei Qiu; Zhenzhen Zhao; Han Wang; Qun Yan (Journal of Hazardous Materials, 2025)

Research on the spatial spillover effects and mechanisms of environmental regulation on the upgrading of WEEE industrial structure - Hongfei Wang; Xiuxia Yan; Caiyun Zhang; Man Yang (Journal of Cleaner Production, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Electrochemical degradation of toluene-2,4-diamine by graphene oxide-modified Ti/Sb-SnO2/α-PbO2/β-PbO2 anode: Performance and mechanism - Shuaishuai Man; Jun Zhang; Hebin Bao; Yifan Ge; Youcun Bai; Xinyu Liu; Ziyang Li; Liwei Qiu; Zhenzhen Zhao; Qun Yan (Environmental Research, 2025)

Advances in multi-omics technologies for identifying metabolic engineering targets and improving lipid production in microalgae - Chun-xiao Yan; Shuai Zhang; Lu-wei Xu; Han Gao; Zi-xu Zhang; Wang Ma; Xiao-man Sun (Bioresource Technology, 2025)

Postharvest fruit rot on blue honeysuckle (Lonicera caerulea L.) caused by Penicillium oxalicum newly reported in China - Haohao Yan; Yuxuan Li; Yusheng Lv; Xin Zhao; Zijian Man; Zexu Chen; Liangchuan Guo; Junwei Huo; Mingyu Sang; Chunyan Li; Hailian Zang; Yi Cheng (Crop Protection, 2025)

High-resolution estimation of urban anthropogenic carbon emissions - Zirong Lin; Bo Huang; Jia He; Yizhen Yan; Man Xiao; Qinrui Luo; Zhulin Qi; Xiaotian Ding (Sustainable Cities and Society, 2025)

Modulating the electronic configuration of single-atom nanozymes using cobalt nanoclusters for enhanced mycotoxin degradation - Yaqi Zhang; Huikang Lin; Lan Wang; Lijun He; Yong Man; Bingxuan Jia; Zheng Yan; Shimo Kang; Haijiao Xie; Aibo Wu (Food Chemistry, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Soil water regulates plant diversity response to gradual and step nitrogen addition - Jiu-Ying Pei; Yang Zheng; Yan Yu; Josep Peñuelas; Jordi Sardans; Man-Qiong Liu; Chao Fang; Wen-Bin Ke; Jian-Sheng Ye (Plant and Soil, 2025)

Effects of air pollution and greenspace exposure on cause-specific mortality among older adults in Guangzhou, China - Bing Bu; Man Chen; Lixian Huang; Yongtao Yan; Jiangchun Yao; Guang-Hui Dong; Ye Liu (Applied Geography, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

How does built environment affect the urban heat Island effect? a systematic framework integrating land use, building form, and road network - Chaohui Yin; Jinlong Yan; Man Yuan; Guohang Tian; Qian Wen; Ling Wang; Ling Li (Environment, Development and Sustainability, 2025)

Retraction notice to “Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica)” [Chemosphere 352 (2024) 141430] - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2025)

Effects of improved quorum sensing signaling system by iron-modified biochar on alleviation of ammonia inhibition during biomethanation - Chujia Lv; Shuaishuai Man; Mohamed Hemida Abd-Alla; Han Wang; Qun Yan (Journal of Environmental Chemical Engineering, 2025)

Degrading hydrophilic PVC and hydrophobic PS microplastics by electrochemical oxidation technology: Comparation for BDD, PbO2, and DSA anodes - Xinyu Liu; Liwei Qiu; Youcun Bai; Xuzhong Zeng; Zhenzhen Zhao; Xinyi Long; Hebin Bao; Yue Zhao; Han Wang; Qun Yan; Shuaishuai Man (Journal of Environmental Chemical Engineering, 2025)

Unveiling the influence of the Afatg3 gene: Autophagy's role in sporulation, aflatoxin synthesis, pathogenicity, and drug stress response in Aspergillus flavus - Yong-xin Li; Yan Ma; Chao Pan; Linchong Hui; Chan Zhang; Man Liu; Kunlong Yang; Xue Peng; Jun Tian (Food Bioscience, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

Cell wall engineering of Yarrowia lipolytica to improve extraction efficiency of functional lipids - Feng Zhang; Yi Zheng; Hong-Yan Jing; Fei Du; Yi-Wen Hang; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Peppermint essential oil: Disruption of cellular structure and function in Listeria monocytogenes - Chun-Ling Yang; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang (Food Bioscience, 2025)

Biomass aerogel: An emerging eco-friendly material for adsorbing pollutants in water - Wei Liu; Chen Dai; Linheng He; Xingyu Liu; Zhiyang Zhao; Wenqian Yan; Man Yuan; Zihao Song; Sheng Cui (Chemical Engineering Journal, 2025)

Solasodine binds to glucocorticoid receptor to ameliorate airway remodeling and excessive autophagy in bronchial smooth muscle cells for allergic asthma - Zhen Guo; Jun-li Liu; Yan-ni Fang; Xiao-man Guo; Chun-long Ma; Jing-wei Wang (Toxicology and Applied Pharmacology, 2025)

Antioxidant and antimicrobial PSE-like chicken protein isolate films loaded with oregano essential oil nanoemulsion for pork preservation - Chen-Yan Zhu; Ke Li; Yu Wang; Man-Ting Du; Bo Chen; Yun-Tao Wang; Yan-Fang Zhou; Yan-Hong Bai (Food Chemistry, 2025)

Ferrihydrite regulated nitrogen metabolic pathway at biocathode of bioelectrochemical system – Insight into biofilm formation and bacterial composition - Zeqi Liu; Xiaojie Liu; Han Wang; Shuaishuai Man; Qun Yan (Bioresource Technology, 2025)

TRMT6 and TRMT61A facilitated acute pancreatitis severity via regulation of neutrophil function - Yuan Dong; Li Su; Sin Man Lam; Cen Yan; Yalan Deng; Guotao Lu; Jinkui Yang; Guanghou Shui; Yingmei Feng (Science China Life Sciences, 2025)

Analysis of the effect of 60 Co irradiation sterilization on the chemical composition of volatile organic compounds in Rhizoma Acori Tatarinowii using GC-IMS - Man-Shu Zou; Li-Yan Xie; Wei Zhou; Yun Xiang; Chang Lei; Dan Huang (Natural Product Research, 2025)

Similarity design method for soil–structure–water models in centrifugal shaking table tests - Yu Chen; Yan-Man Liu; Kun Wu; Xin Huang (Soil Dynamics and Earthquake Engineering, 2025)

Sustainable high-performance density—nanoporous composite wood for water evaporation-induced electricity generation - Man Yi Wong; Abhishek Gautam; Kaixin Lin; Jianheng Chen; Tsz Chung Ho; Muhammad Fahim; Xu Chen; Aiqiang Pan; Chi Yan Tso (Chemical Engineering Journal, 2025)

Effects of postbiotics produced by Lactobacillus plantarum JM015 isolated from traditional fermented dairy products on Salmonella-induced intestinal inflammation: A preventive strategy - Lidong Pang; Yan Huang; Runze Li; Ling Guo; Chaoxin Man; Xinyan Yang; Yujun Jiang (Food Chemistry, 2025)

MXene@MnO2 hybrid as durable ‘brick-mud’ coatings for fabricating anti-bacterial textiles with HCHO removal capacity - Xueming Bao; Leilei Wu; Biaobiao Yan; Ying Liu; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2025)

Correlation between the structures of natural polysaccharides and their properties in regulating gut microbiota: Current understanding and beyond - Wing-Shan Keung; Wei-Hao Zhang; Han-Yan Luo; Kam-Chun Chan; Yui-Man Chan; Jun Xu (Carbohydrate Polymers, 2025)

Accelerating repair of infected bone defects through post-reinforced injectable hydrogel mediated antibacterial/immunoregulatory microenvironment at bone-hydrogel interface - Zheng Wang; Ying Chu; Jingyi Du; Yan Hu; Huimin Wang; Hanghang Liu; Changying Yang; Man Wang; Jiabing Ran; Aixi Yu (Carbohydrate Polymers, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Diagnostic accuracy of Xpert MTB/RIF Ultra for detecting pulmonary tuberculosis and rifampicin resistance: a systematic review and meta-analysis - Man-Qing Wang; Ya-Fang Zheng; Yu-Qi Hu; Jin-Xia Huang; Zi-Xin Yuan; Zu-Yan Wu; Lu-Fang Huang; Chu-Ting Tang; Feng-Yi Zhang; Yan Chen; Jin-Ke He; Xu-Guang Guo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A pathway to empower rural resilience through rural computing: An exploratory study - Wei Lang; Eddie Chi-man Hui; Tingting Chen; Yan Huang (Applied Geography, 2025)

Composition, structure and comprehensive utilization of abalone shell: A review - Man-Yu Li; Yan-Chao Wu; Li Huang; Pi-Xian Gong; Hui-Jing Li (Sustainable Chemistry and Pharmacy, 2025)

Deposition behavior of PbTe doped LBE aerosol and Te valence prediction: Platform test and First-principles calculation - Yuqing Wang; Hui Du; Yi Tan; Yan Chen; Futing Jing; Jiewei Wu; Yingwu Jiang; Hanyu Wu; Fuhao Ji; Muyi Ni; Man Jiang (Journal of Hazardous Materials, 2025)

Simultaneous tributyl phosphate (TBP) removal and P recovery through electro-Fenton (EF): Process exploring and mechanism probing - Liwei Qiu; Xuzhong Zeng; Fang Guo; Chaoyun Wang; Han Wang; Zhenzhen Zhao; Shuaishuai Man; Qun Yan (Journal of Environmental Chemical Engineering, 2025)

Characterization and application of Schizochytrium sp. HX-308 promoters for enhanced docosahexaenoic acid biosynthesis - Chun-Xiao Yan; Yi Zheng; Shuai Zhang; Zi-Jia Li; Zi-Xu Zhang; Ying-Shuang Xu; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Coupling ultrasound and low temperature stress for enhancing Docosahexaenoic acid production in Schizochytrium sp. - Chun-Xiao Yan; Shuai Zhang; Kai-Nan Zhang; Fei Du; Wang Ma; Xiao-Man Sun (Food Bioscience, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Intestinal Flatulence in Pampus argenteus: Changes in Gut Microbiota - Wenhao Nie; Man Zhang; Youyi Zhang; Yuanbo Li; Shanliang Xu; Jiabao Hu; Yajun Wang; Xiaojun Yan (Journal of Ocean University of China, 2025)

Effects of supplemental medusa ( Rhopilema esculentum ) on intestinal microbiota and metabolites in silver pomfret ( Pampus argenteus ) - Man Zhang; Mengke Tang; Kaiheng Yan; Youyi Zhang; Yaya Li; Jie Tang; Shanliang Xu; Xiaojun Yan; Jiabao Hu; Yajun Wang (Journal of Fish Biology, 2025)
Pampus argenteus demonstrates a preference for Rhopilema esculentum as prey, yet the ramifications of consuming supplemental medusa on fish microbiota and metabolism remain elusive. To elucidate these effects, 300 juvenile fish were divided into two groups: control group (C, given commercial food only) and supplemental medusa (SM) group (given supplemental medusa + commercial feed). After 15 days, fish in the SM group exhibited a significant increase in fatness, the amylase activity in the intestine significantly increased, and the intestinal microvilli were arranged more neatly. The comprehensive approach involving 16S rRNA amplicon sequencing and metabolomics was employed, leading to the identification of five genera within the SM group, namely Lactococcus , Cohaesibacter , Maritalea , Sulfitobacter , and Carnobacterium . Functional prediction analysis of the microbiota indicated that the consumption of supplemental medusa facilitated processes such as glycolysis/gluconeogenesis and amino acid absorption. Metabolomics analysis revealed significant enrichment of 85 differential metabolites, most of them belonging to fatty acids and conjugates. These differential metabolites primarily participated in processes such as amino acid metabolism, fatty acid synthesis, and disease. Notably, the consumption of medusa resulted in a significant reduction in nine lysophospholipids associated with cardiovascular disease and inflammation. Pearson's correlation coefficient analysis revealed associations between specific microorganisms and metabolites, indicating that Cobetia , Weissella , and Macrococcus exhibited an increased abundance in the SM group, positively correlating with apocynin, 12‐Hete, and delta 9‐THC‐d3. The indicator bacteria Psychrobacter reduced in the SM group, exhibiting a negative correlation with cystathionine (a compound involved in glutathione synthesis). Overall, the supplementation of medusa may confer a beneficial effect on the immunity of the fish. This study contributes to the theoretical framework for fish feed development.

Corrigendum to “Hydrogen peroxide as a mitigation against Microcystis sp. Bloom” [Aquaculture, Volume 577, 15 December 2023, 739932] - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Deciphering the distinct roles of polyketide synthase subunits in polyunsaturated fatty acid and lipid accumulation in Schizochytrium sp. - Hong-Xuan Wu; Wen-Qian Yang; Zi-Xu Zhang; Yan-Cheng Lin; Wang Ma; Xiao-Man Sun; He Huang (Food Bioscience, 2025)

Timing of magnetite introduction drives distinct community succession in bioelectrochemical systems: From colonization to acclimation - Ziang Kong; Han Wang; Shuaishuai Man; Qun Yan (Chemical Engineering Journal, 2025)

Detecting the Phaeocystis globosa bloom and characterizing its bloom condition in the northern Beibu Gulf using MODIS measurements - Jie Li; Junxiang Lai; Guilin Xu; Mingben Xu; Man Wu; Xiaomin Yan; Zihan Pan; Jing Guo (Marine Pollution Bulletin, 2024)

Spatial distribution, chemical speciation and source apportionment of carbon, nitrogen and phosphorus in surface sediments of northern Beibu Gulf, South China - Jing Guo; Xiaomin Yan; Man Wu; Hengtong Qiu; Wan-Yi Li; Wenlong Huang; Di Wu; Baoming Xue; Guilin Xu; Zihan Pan; Zhiming Mo (Marine Pollution Bulletin, 2024)

A systematic workflow of data mining confirms widespread ecological risks of SDHIs fungicides contamination in aquatic environment - Xi-Yan Xu; Man-Man Duan; Jia-Yi Zhou; Yuan-Bo Li; Yong-Quan Zheng; Yang Yang (Science of The Total Environment, 2024)

Screening of metal-modified biochars for practical phosphorus recovery - Man Li; Qian Xie; Fangxi Xu; Yan Zhang; Zechao Zhuang; Jiawei Xu; Hai Xiang; Yongfu Li; Yanjiang Cai; Zuliang Chen; Bing Yu (Science of The Total Environment, 2024)

Comparative analysis of lipid composition in colostrum and mature milk from women of seven Chinese ethnic groups - Zhiyi Zhang; Teng Wei; Xinggang Ni; Ting Li; Ignatius Man-Yau Szeto; Sufang Duan; Yalu Yan; Wenhui Ye; Jing Li; Zeyuan Deng (International Dairy Journal, 2024)

Application of Cytochrome P450 Monooxygenases in Plant for Rapid Detection of 2,3,7,8 Tetrachlorodibenzodioxin in the Contaminated Sites - Ho Man Leung; Ka Chun Sung; Lai Yan Woo; Wing Yin Mo; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Assessment of Spatial Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils and Fungal Disease Status of Trees Grown in Hong Kong Areas - Ka Chun Sung; Ho Man Leung; Chi Fung Lee; Tohidi Fatemeh; Wing Yin Mo; Lai Yan Woo; Kwai Chung Cheung; Uchenna Ogbonnaya; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Identification of major histocompatibility complex II gene in Pampus argenteus and the expression pattern in Pampus argenteus kidney cell line under the pathogen stress - Youyi Zhang; Jiabao Hu; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Zi Yuan; Xiaomei Sun; Lu Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Transcriptome analysis identified a transcriptional repressor, BES1-INTERACTING MYC-LIKE1 regulating rapid postharvest fruit softening of Actinidia arguta - Jian Wang; Xue-mei Lu; Mei-mei Kuang; Yuan-qiang Zhang; Yu-ping Man; Wen-qiu Wang; Yan-chang Wang (Postharvest Biology and Technology, 2024)

Corrigendum to “Association of urban green space with metabolic syndrome and the role of air pollution” [Landsc. Urban Plann. 248 (2024) 105100] - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

Evaluating the binding mechanism, structural changes and stability of ternary complexes formed by the interaction of folic acid with whey protein concentrate-80 and L-ascorbyl 6-palmitate - Xiaodong Wang; Zengbo Wang; Kangyong Zhang; Ignatius Man-Yau Szeto; Yalu Yan; Biao Liu; Jie Zhang; Smith Etareri Evivie; Bailiang Li; Sufang Duan (Food Chemistry, 2024)

Enhancing Bone-Titanium integration through hydrogel coating mediated sequential M1/M2 polarization of interfacial macrophages - Zheng Wang; Honghan Yan; Man Wang; Yan Hu; Hao Zeng; Hanghang Liu; Huimin Wang; Changying Yang; Jin Liu; Aixi Yu; Jiabing Ran (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

RETRACTED: Assessing exposure risk to microplastics by Indian Ocean pygmy blue whales - Mengyang Liu; Keran Yang; Naomi Brannan; Hoi Man Liu; Enoka Kudavidanage; Minggang Cai; Haowen Zheng; Kai Zhang; Shaopeng Xu; Meng Yan; Kenneth M.Y. Leung; Lindsay Porter (Aquatic Toxicology, 2024)

Response Mechanism of Dynamic Tensile Mechanics in Granite Under Microwave Irradiation: Insights from Experiments and Simulations - Bo-Wen Sun; Sheng-Qi Yang; Man Huang; Heng Li; Wen-Ling Tian; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Excitotoxic Storms of Ischemic Stroke: A Non-neuronal Perspective - Xiao-man Yang; Hao Yu; Jia-xin Li; Na Li; Chong Li; Dong-han Xu; Hao Zhang; Tian-he Fang; Shi-jun Wang; Pei-yu Yan; Bing-bing Han (Molecular Neurobiology, 2024)

Photoelectron-transfer-effect grafting: Validation of a generalized strategy for fluorescence and photoelectrochemical dual-mode detection of hydrogen sulfide - Xiao-Jie Yu; Xiao-Yan Wan; Yu-Ting Shen; Deng-Bao Zhang; Xian-Jing Zhou; De-Man Han; Feng-Zao Chen (Analytica Chimica Acta, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

The changes in HMOs of GDM mothers over lactation: Regulation on the gut microbiota development in offspring - Lina Zhang; Jinyue Zhang; Yalu Yan; Sufang Duan; Xuemin Wang; Ignatius Man-Yau Szeto; Jun Liu; Zhaona Sun; Xiang Feng; Kasper Hettinga; Peng Zhou (Food Bioscience, 2024)

A sustainable approach: Repurposing harmful algal biomass as carbon-based catalysts for nitrogen fertilizer electrosynthesis from nitrate and CO2 - He Wang; Shuaishuai Man; Han Wang; Volker Presser; Qun Yan (Chemical Engineering Journal, 2024)

Experimental Study on Mechanical Behavior, Fracture Characteristics, and Acoustic Emission Damage Characteristics of Sandstone Under Triaxial Multistage Stress Disturbance - Sheng-Qi Yang; Jing Yang; Zong-Long Mu; Guang-Jian Liu; Man Huang; Ke-Sheng Li; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Research on mine water source classifications based on BO-CatBoost - Han Li; Zhenwei Yang; Hang Lv; Man Wang; Bo Zhang; Hengrui Yan; Hongyu Zhang (Environmental Monitoring and Assessment, 2024)

Simulated cold spell: Changes of lipid metabolism on silver pomfret during cooling and rewarming - Man Zhang; Jiabao Hu; Jiajie Zhu; Mengke Tang; Youyi Zhang; Yaya Li; Weiwei Gu; Huan Jiang; Danli Wang; Shanliang Xu; Xiaojun Yan; Yajun Wang (Aquaculture, 2024)

Tenascin can inhibit apoptosis induced by copper in silver pomfret (Pampus argenteus) - Jiabao Hu; Youyi Zhang; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Rongyue Zheng; Shanliang Xu; Yajun Wang; Xiaojun Yan (Aquaculture, 2024)

Magnetite-mediated shifts in denitrifying consortia in bioelectrochemical system: Insights into species selection and metabolic dynamics - Ziang Kong; He Wang; Han Wang; Shuaishuai Man; Qun Yan (Water Research, 2024)

Immunosuppressive leucosesterterpane and penta-nor-leucosesterterpane sesterterpenoids from Leucosceptrum canum - Ting-Ting Zhou; Man-Wen Zhang; Yan-Chun Liu; Xiao-Nian Li; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Association of urban green space with metabolic syndrome and the role of air pollution - Yi Sun; Yunli Chen; Yuanyuan Huang; Yan Luo; LiPing Yan; Sailimai Man; Canqing Yu; Jun Lv; Chuangshi Wang; Jun Wu; Heling Bao; Bo Wang; et al. (Landscape and Urban Planning, 2024)

In-situ biogenic FeS boosted acetate accumulation through CO2 capture and valorization using microbial electrosynthesis (MES) - Huixing Wu; Lingyan Ding; Han Wang; Shuaishuai Man; JunRae Kim; Liwei Qiu; Qun Yan (Chemical Engineering Journal, 2024)

Policy impact of national comprehensive pilot initiative for new-type urbanization on carbon emissions from rural energy consumption in China - Man Wang; Manman Gao; Huimin Cao; Zhenyu Yan; Muhammad Taimoor; Jiapeng Xu (Environment, Development and Sustainability, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

AhR agonists screening and identification in indoor dust based on non-target chemical analysis by GC-Q-TOFMS and biological effect evaluation referring to ToxCast/Tox21 database - Chaoli Yuan; Yuqi Zeng; Xiaomin Yan; Jiwen Luo; Lixuan Zeng; Yu Bon Man; Bingyan Lan; Yuan Kang (Chemosphere, 2024)

Applications of charcoal, activated charcoal, and biochar in aquaculture – A review - Chun Fung Wong; Uddin Md Saif; Ka Lai Chow; James Tsz Fung Wong; Xun Wen Chen; Yan Liang; Zhang Cheng; Yiu Fai Tsang; Ming Hung Wong; Yu Bon Man (Science of The Total Environment, 2024)

How α -lactalbumin and β –casein level in infant formula influence the protein and minerals absorption properties by using Caco-2 cell model - Mengyu Han; Xuemin Wang; Kai Zhang; Ignatius Man-Yau Szeto; Sufang Duan; Yalu Yan; Biao Liu; Kasper Hettinga; Lina Zhang; Peng Zhou (Food Bioscience, 2024)

Identification and characterization of STAT family in silver pomfret (Pampus argenteus) involved in different exogenous stresses - Wenhao Nie; Yuanbo Li; Youyi Zhang; Man Zhang; Yaya Li; Shanliang Xu; Jiabao Hu; Yajun Wang; Xiaojun Yan (Fish & Shellfish Immunology, 2024)

High-spatial resolution ground-level ozone in Yunnan, China: A spatiotemporal estimation based on comparative analyses of machine learning models - Xingwei Man; Rui Liu; Yu Zhang; Weiqiang Yu; Fanhao Kong; Li Liu; Yan Luo; Tao Feng (Environmental Research, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Adult hair follicle stem cells differentiate into neuronal cells in explanted rat intestinal tissue - Zuyin Sun; Jiashi Huo; Yongshen Tian; Mei Liu; Yan Liu; Man Xu; Qiyou Yin (In Vitro Cellular & Developmental Biology - Animal, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Subtypes of Blastocystis in Tibetan Antelope (Pantholops hodgsonii) - Wei-Lan Yan; Xiao-Man Li; Si-Yuan Qin; Nian-Yu Xue; Yang Zou; Jing-Hao Li; Xiao-Xuan Zhang; Hong-Bo Ni (Research in Veterinary Science, 2024)

Nutrient budgets and biogeochemical dynamics in the coastal regions of northern Beibu Gulf, South China Sea: Implication for the severe impact of human disturbance - Jing Guo; Fei Yang; Ozeas S. Costa; Xiaomin Yan; Man Wu; Hengtong Qiu; Wanyi Li; Guilin Xu (Marine Environmental Research, 2024)

Vibrational modes of guest in sH hydrate based on in situ Raman spectroscopy and density functional theory - Man Li; Yang Zhao; Lei Yang; Yan Su; Jiafei Zhao; Amadeu K. Sum; Yongchen Song (Fuel, 2024)

Over 30% external quantum efficiency for doping-free D-A-type thermally activated delayed fluorescence organic light-emitting diodes - Yang Li; Yixia Liu; Yang Gao; Kai Zhang; Yan-Qiu Sun; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2024)

Blue electroluminescence from homoleptic Ir(III) carbene phosphors and peripheral decorated multiple resonance boron emitters - Jie Yan; Takeru Nakamura; Xiaolan Tan; Shek-Man Yiu; Ryunosuke Mimura; Keigo Hoshi; Xiuwen Zhou; Yun Chi; Hisahiro Sasabe; Junji Kido (Chemical Engineering Journal, 2024)

Breathable and washable MXene@gallic acid cross-linked textile assisted by borax for personal multi-protection wearables - Biaobiao Yan; Xiaoting Liao; Tianlei Sun; Leilei Wu; Zhenfei Guo; Man Zhou; Yuanyuan Yu; Qiang Wang; Chaobin He; Ping Wang (Chemical Engineering Journal, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

Effect of suspended solids from anaerobic digested wastewater on performance and microbial community of autotrophic nitrogen removal process - Yan Huang; Longxing Jiang; Bo Wu; Jiaxin Liu; Yi Liu; Ling Xie; Man Zhou; Liangwei Deng; Wenguo Wang; Lan Wang (Journal of Cleaner Production, 2024)

Three-dimensional discrete element simulation of the triaxial cyclic loading of sandstone based on a nonlinear parallel-bonded stress corrosion model - Ming-Hui Cao; Sheng-Qi Yang; Wen-Ling Tian; Yan-Hua Huang; Man Huang (Computers and Geotechnics, 2024)

Transcriptomic analysis and oxidative stress induced by sodium dichloroisocyanurate in the intestine of Phascolosoma esculenta - Peifen Hu; Huijing Peng; Xiao Man; Zenghou Xing; Chongyang Wang; Congyan Yu; Jiamin Xing; Xueyu Yan; Hong Zhang; Mengqing Zeng; Lei Bao; Jie Zou; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Characterization of the MIKCC-type MADS-box gene family in blueberry and its possible mechanism for regulating flowering in response to the chilling requirement - Sui-Lin Zhang; Yan Wu; Xiao-Han Zhang; Xin Feng; Hui-Ling Wu; Bing-Jie Zhou; Ya-Qian Zhang; Man Cao; Zhi-Xia Hou (Planta, 2024)

RETRACTED: Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica) - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2024)

Immune strategies of silver pomfret (Pampus argenteus) infected with Nocardia seriolae at different infection stages - Youyi Zhang; Jiabao Hu; Yuanbo Li; Feirong Yuan; Kaiheng Yan; Weiwei Gu; Man Zhang; Yaya Li; Xiang Huang; Cheng Zhang; Dingyuan Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Retraction Notice to “Risk-involved stochastic scheduling of plug-in electric vehicles aggregator in day-ahead and reserve markets using downside risk constraints method” [Sustainable Cities and Society 55 (2020) 102051] - Man-Wen Tian; Shu-Rong Yan; Xiao-Xiao Tian; Milad Kazemi; Sayyad Nojavan; Kittisak Jermsittiparsert (Sustainable Cities and Society, 2024)

An effective approach for Yangtze river vessel traffic flow forecasting: A case study of Wuhan area - Jie Man; Deshan Chen; Bing Wu; Chengpeng Wan; Xinping Yan (Ocean Engineering, 2024)

A microfluidic concentration gradient colorimetric system for rapid detection of nitrite in surface water - Yan Man; Kaijia Yu; Huimin Tan; Xinxin Jin; Jing Tao; Ligang Pan (Journal of Hazardous Materials, 2024)

Bioaccessibility of docosahexaenoic acid in naturally and artificially enriched milk - Pengjie Wang; Panqiao Chen; Xiaoxu Zhang; Ignatius Man-Yau Szeto; Fang Li; Shengjie Tan; Genna Ba; Yan Zhang; Sufang Duan; Yue Yang (Food Chemistry, 2024)

Tryptophan sulfonate: A new chemical marker for accurate and efficient inspection of sulfur-treated food products - Kam-Chun Chan; Wei-Hao Zhang; Yui-Man Chan; Hiu-Lam Li; Jing Fang; Han-Yan Luo; Jun Xu (Food Chemistry, 2024)

Two new thymol derivatives from Eupatorium fortunei - Jing Shi; Yan-peng Dai; Min Yuan; Xiao-man Sun; Chuan-jie Song; Yu-guo Liu (Natural Product Research, 2024)

VX-765 Alleviates Circadian Rhythm Disorder in a Rodent Model of Traumatic Brain Injury Plus Hemorrhagic Shock and Resuscitation - Yan Li; Yue Xin; Man-Man Qi; Zhi-You Wu; Han Wang; Wei-Chao Zheng; Jie-Xia Wang; Dong-Xue Zhang; Li-Min Zhang (Journal of Neuroimmune Pharmacology, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Immune response of silver pomfret (Pampus argenteus) to Photobacterium damselae subsp. Damselae: Virulence factors might induce immune escape by damaging phagosome - Youyi Zhang; Jiabao Hu; Kaiheng Yan; Feirong Yuan; Yuanbo Li; Man Zhang; Yaya Li; Xiang Huang; Jie Tang; Danli Wang; Shanliang Xu; Suming Zhou; et al. (Aquaculture, 2024)

Microbial regulation of aggregate stability and carbon sequestration under long-term conservation tillage and nitrogen application - Mengni Zhang; Xiaojun Song; Xueping Wu; Fengjun Zheng; Shengping Li; Yan Zhuang; Xvlun Man; Aurore Degré (Sustainable Production and Consumption, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Stable carbon isotopes and stomatal frequency of Middle Jurassic ginkgophyte fossils from the Turpan basin, northwestern China: Implications for reconstructing paleo-CO2 changes - Liang Xiao; Jia-qi Liang; Li-yan Guo; De-shuang Ji; Man Yuan; Xiang-chuan Li; Nan Sun; Zuo-chen Li (Journal of Asian Earth Sciences, 2024)

Antifungal effects of carvacrol, the main volatile compound in Origanum vulgare L. essential oil, against Aspergillus flavus in postharvest wheat - Wen-Yan Duan; Xi-Man Zhu; Shuai-Bing Zhang; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu (International Journal of Food Microbiology, 2024)

Atomic-level surface modification of ultrathin Bi2WO6 nanosheets for boosting photocatalytic CO2 reduction - Lulu Zhao; Huilin Hou; Lin Wang; Chris R. Bowen; Jinguo Wang; Ruifang Yan; Xiaoqiang Zhan; Hongli Yang; Man Yang; Weiyou Yang (Chemical Engineering Journal, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Hydrogen peroxide as a mitigation against Microcystis sp. bloom - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2023)

Comparative proteomics reveals the antibiotic resistance and virulence of Cronobacter isolated from powdered infant formula and its processing environment - Danliangmin Song; Xuehe Qi; Yan Huang; Ai Jia; Yaqi Liang; Chaoxin Man; Xinyan Yang; Yujun Jiang (International Journal of Food Microbiology, 2023)

Enhancing electromagnetic wave absorption performance through co-regulation of microstructure and spatial orientation of RE-Ni MOF - Wei Zhang; Guoguo Tan; Jiaxun Hu; QiWei Wang; Weiran Yan; Qikui Man (Chemical Engineering Journal, 2023)

Change and Regulation of Nutritional Metabolism in Silver Pomfret During Compensatory Growth - Jiabao Hu; Youyi Zhang; Kaiheng Yan; Man Zhang; Yaya Li; Yuanbo Li; Weiwei Gu; Shanliang Xu; Yajun Wang; Xiaojun Yan (Marine Biotechnology, 2023)

Cold Stress Induces Apoptosis in Silver Pomfret via DUSP-JNK Pathway - Jiabao Hu; Man Zhang; Kaiheng Yan; Youyi Zhang; Yaya Li; Jiajie Zhu; Guanlin Wang; Xiangbing Wang; Yuanbo Li; Xiang Huang; Jie Tang; Rongyue Zheng; et al. (Marine Biotechnology, 2023)

Effect of ozone nanobubbles on the microbial ecology of pond water and safety for jade perch (Scortum barcoo) - Qianjun Huang; Pok Him Ng; Ana Rita Pinheiro Marques; Tzu Hsuan Cheng; Ka Yan Man; Kwok Zu Lim; Brett MacKinnon; Liqing Huang; Ju Zhang; Ladan Jahangiri; William Furtado; F.M. Yasir Hasib; et al. (Aquaculture, 2023)

Dissecting the genetic basis of grain weight and size in common oat by genome-wide association study - Honghai Yan; Di Deng; Pingping Zhou; Yun Peng; Xiaolong Dong; Shuchang Li; Yongjie Zhang; Qin Man; Ziqin Lv; Tao Chen; Changzhong Ren; Yuanying Peng (Journal of Cereal Science, 2023)

Improved sample preparation method on the morphology observation of hydrophilic polysaccharides for atomic force microscopy (AFM) - Sicong Yan; Shuai Yuan; Qian Zhang; Man Luo; Dongling Qiao; Fatang Jiang; Hong Qian (Food Hydrocolloids, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Examination of the effects of dry storage stress on mitochondrial energy synthesis in the scallop Mizuhopecten yessoensis - Zhongzhuan Yin; Man Li; Yan Cai; Lin Qi; Chunhong Yuan; Yuanyong Tian (Aquaculture, 2023)

Identification and characterization of toll-like receptor genes in silver pomfret (Pampus argenteus) and their involvement in the host immune response to Photobacterium damselae subsp. Damselae and Nocardia seriolae infection - Yuanbo Li; Jiabao Hu; Youyi Zhang; Kaiheng Yan; Man Zhang; Yaya Li; Xiang Huang; Jie Tang; Tingyan Yao; Danli Wang; Shanliang Xu; Xubo Wang; et al. (Fish & Shellfish Immunology, 2023)

Thienoacene-fused fluorophores for highly efficient deep red/near-infrared OLEDs - Li Zhu; Yixia Liu; Xiaofei Wang; Kai Zhang; Jing-Wen Tai; Yan-Qiu Sun; Chuan-Kui Wang; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2023)

Magma process of the ore-forming gabbrodiorite porphyry of the Meishan iron deposit, eastern China: Insights from the phenocrysts chemistry - Wen-Hao Liu; Man-Rong Jiang; Yan Xia; Xiao-Jun Zhang (Journal of Geochemical Exploration, 2023)

Gypenosides suppress hepatocellular carcinoma cells by blocking cholesterol biosynthesis through inhibition of MVA pathway enzyme HMGCS1 - Man-Yu Xiao; Fang-Fang Li; Peng Xie; Yan-Shuang Qi; Jin-Bo Xie; Wen-Jing Pei; Hao-Tian Luo; Mei Guo; Yu-Long Gu; Xiang-Lan Piao (Chemico-Biological Interactions, 2023)

Study on the ditching of space capsules using the smoothed particle hydrodynamics method - Xin-Yang Ju; Peng-Nan Sun; Yan-Ming Shen; Jian-Qiang Chen; A-Man Zhang (Ocean Engineering, 2023)

Characterizing the remobilization flux of cadmium from pre-anthesis vegetative pools in rice during grain filling using an improved stable isotope labeling method - Bo-Fang Yan; Cheng-Feng Hu; Man Zhao; Rong-Liang Qiu; Ye-Tao Tang (Environmental Pollution, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Synthesis of branched cationic flocculant and its performance in treating industrial wastewater with different compositions - Xiaoli Ren; Xiujun Wang; Jian Zhang; Ming Duan; Yan Xiong; Shenwen Fang; Man Shi (Journal of Water Process Engineering, 2023)

Global and regional trends in greenhouse gas emissions from rice production, trade, and consumption - Xiang Wang; Xiaoyan Chang; Libang Ma; Jing Bai; Man Liang; Simin Yan (Environmental Impact Assessment Review, 2023)

OsTST1, a key tonoplast sugar transporter from source to sink, plays essential roles in affecting yields and height of rice (Oryza sativa L.) - Man-Yu Yang; Xiu Yang; Zhen Yan; Qing Chao; Jie Shen; Guang-Hou Shui; Peng-Mei Guo; Bai-Chen Wang (Planta, 2023)

Effects of different photoperiods on growth and ovarian development and maturation of silver pomfret Pampus argenteus - Xiangbing Wang; Yaya Li; Jiabao Hu; Youyi Zhang; Man Zhang; Guanlin Wang; Huan Jiang; Jiachu Sun; Chunyang Guo; Shanliang Xu; Yang Yang; Yajun Wang; et al. (Journal of Fish Biology, 2023)
Photoperiod has a great influence on the growth and ovarian development and maturation of fishes. To analyse the effects of photoperiod on growth and ovarian development of an important marine economic fish, silver pomfret Pampus argenteus , short photoperiod group (L:D = 8:16), control group (L:D = 12:12) and long photoperiod group (L:D = 18:6) were set up for 60 days. The growth performance, ovarian development, changes in hormones and key enzyme activities in the hypothalamic–pituitary−gonadal (HPG) axis and expressions of key regulatory genes in the HPG axis were studied under different photoperiod conditions. The results showed that the final weight gain, body weight index, specific growth rate for weight, specific growth rate for length and average daily growth were the highest in the long photoperiod group, and the feed conversion rate was the lowest. Under long photoperiod condition, gonado‐somatic index and hepato‐somatic index were higher, ovarian maturity was better and expressions of HPG axis−related regulatory genes foxl2a , foxl2b , cyp19a1a , cyp19a1b , kiss , gpr54‐2 , gnrh2 , fsh and lh were higher. When compared with the other two groups, in the long photoperiod group, the change trend of estradiol (E2) was consistent with those of luteinizing hormone, melatonin (MT) and kisspeptin, and the levels were higher on the 20th and 50th days. These results indicate that prolongation of the photoperiod can improve the growth performance of P. argenteus and promote ovary development and maturation. The authors speculate that photoperiod may regulate the ovarian activity of P. argenteus through MT and kisspeptin/gpr54 signalling pathways. The results show that photoperiod can regulate the ovarian development of P. argenteus , which would help in breaking the seasonal restrictions of animals and regulating an animal's reproductive cycle.

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Integrative transcriptome and metabolome revealed the molecular mechanism of Bacillus megaterium BT22-mediated growth promotion in Arabidopsis thaliana - Xiao Liu; Yan Du; Xiaofan Na; Man Wang; Ying Qu; Linghui Ge; Yuanmeng Wang; Linqi Gao; Wenke Bai; Yurong Bi; Libin Zhou (Journal of Plant Physiology, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Influence of Cathode Modification by Chitosan and Fe3+ on the Electrochemical Performance of Marine Sediment Microbial Fuel Cell - Xuerong Zai; Man Guo; Xiang Huang; Huaijing Zhang; Yan Chen; Hongwei Ji; Yubin Fu (Journal of Ocean University of China, 2023)

Intermolecular interactions and gel properties of composite agglomerative networks based on oppositely charged polymers: Effects of pH and ionic strength - Xinyue Yan; Yijia Jia; Hui Man; Lu Liu; Shiyan Sun; Baokun Qi; Yang Li (Food Hydrocolloids, 2023)

Histopathology, immunoenzyme activity and transcriptome analysis of immune response in silver pomfret infected by cryptokaryon (Cryptorchidism irritant) - Guanlin Wang; Jiabao Hu; Man Zhang; Youyi Zhang; Yaya Li; Huang Jiang; Xiangbing Wang; Jiajie Zhu; Shanliang Xu; Yajun Wang; Xiaojun Yan (Fish & Shellfish Immunology, 2023)

Unraveling the contribution of valence state to the NO oxidation activity of manganese oxides - Zhiyu Qi; Bo Chen; Baochang Man; Zhengwen Li; Kai Feng; Binhang Yan; Guohua Luo (Chemical Engineering Journal, 2023)

Long-term waterborne Cu2+ exposure affects collagen metabolism in fish - Youyi Zhang; Feirong Yuan; Kaiheng Yan; Man Zhang; Yaya Li; Guanlin Wang; Huan Jiang; Xiangbin Wang; Jiajie Zhu; Jiachu Sun; Shanliang Xu; Jiabao Hu; et al. (Aquatic Toxicology, 2023)

Label-free and selective cholesterol detection based on multilayer functional structure coated fiber fabry-perot interferometer probe - Ruiduo Wang; Minglu Yan; Man Jiang; Yang Li; Xin Kang; Mingxuan Hu; Beibei Liu; Zhengquan He; Depeng Kong (Analytica Chimica Acta, 2023)

Detection of Laodelphax striatellus (small brown planthopper) based on improved YOLOv5 - Wenxuan Huang; Yan Huo; Shaochen Yang; Mingjia Liu; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2023)

Restored vegetation is more resistant to extreme drought events than natural vegetation in Southwest China - Ying Liu; Zhi Ding; Yanan Chen; Fengqin Yan; Pujia Yu; Weidong Man; Mingyue Liu; He Li; Xuguang Tang (Science of The Total Environment, 2023)

Comparison of thermal and non-thermal extraction methods on free and bound phenolics in pomegranate peel - Guowei Man; Yan Ma; Lei Xu; Xiaojun Liao; Liang Zhao (Innovative Food Science & Emerging Technologies, 2023)

Impact of casein-to-whey protein ratio on gastric emptying, proteolysis, and peptidome profile of fermented milk during in vitro dynamic gastrointestinal digestion in preschool children - Hongyan Zhang; Sufang Duan; Yang Yu; Ren'an Wu; Jingjing Wang; Xiao Dong Chen; Ignatius Man-Yau Szeto; Peng Wu; Yan Jin (Food Chemistry, 2023)

The Effect of Schizochytrium sp. on Growth, Fatty Acid Profile and Gut Microbiota of Silver Pomfret (Pampus argenteus) - Yuanbo Li; Qijun Le; Man Zhang; Shanliang Xu; Shan He; Xiaojun Yan; Jiabao Hu; Yajun Wang (Journal of Marine Science and Engineering, 2023)
Schizochytrium sp. is a kind of heterotrophic protist, rich in docosahexaenoic acid (DHA). To study the application value of Schizochytrium sp. in fish diet, a 20-day feeding experiment was initiated to evaluate its effect on growth, fatty acid contents, and the gut microbiota of the important economic fish, silver pomfret. In this study, the diets of the treatment group were added with 2% Schizochytrium sp. The fish in the treatment group gained more weight and had a higher growth rate than the control group. The levels of DHA, eicosapentaenoic acid, and polyunsaturated fatty acids in the edible tissue of fish were highly increased in the treatment group after 20 days. After feeding Schizochytrium sp., high-throughput 16S rRNA sequencing showed that the Proteobacteria, Firmicutes and Bacteroidetes were the phyla with the highest abundance, and at the genus and species level, we observed an increased abundance of probiotics. The results indicated that ingestion of Schizochytrium sp. could change the dominant microbiota population, which might lead to accelerated growth and improved unsaturated fatty acid content and fish health. This study provides a reference for Schizochytrium sp. supplementation in fish diets and could aid in the industrialization of silver pomfret.

Labdane diterpenoids from the heartwood of Leucosceptrum canum that impact on root growth and seed germination of Arabidopsis thaliana - Yan Liu; Yan-Ying Zhou; Shi-Hong Luo; Kai Guo; Man-Wen Zhang; Shu-Xi Jing; Chun-Huan Li; Juan Hua; Sheng-Hong Li (Phytochemistry, 2023)

Effects of refrigerated storage on the functional properties of processed cheese analogue with stretchability and its mechanisms - Mengyuan Guo; Zhaoyue Sheng; Pengjie Wang; Yan Zhang; Xiaoying Zhang; Ying Zhang; Ignatius Man-Yau Szeto; Yilun Wang; Fazheng Ren; Jie Luo (International Dairy Journal, 2023)

Tracking the driving forces for the unfolding and folding of kidney bean protein isolates: Revealing mechanisms of dynamic changes in structure and function - Xinyue Yan; Yijia Jia; Hui Man; Shiyan Sun; Yuyang Huang; Baokun Qi; Yang Li (Food Chemistry, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Contrasting effects of elevated CO2 on autotrophic prokaryotes with different CO2 fixation strategies in tea plantation soil - Man Shi; Jiangye Li; Ruonan Gao; Xinzhang Song; Guibin Wang; Yan Gao; Shaohua Yan (Biology and Fertility of Soils, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Confining CoTe2-ZnTe heterostructures on petal-like nitrogen-doped carbon for fast and robust sodium storage - Ying Jiang; Feng Wu; Zhengqing Ye; Yaozong Zhou; Yan Chen; Yixin Zhang; Zekai lv; Li Li; Man Xie; Renjie Chen (Chemical Engineering Journal, 2023)

Plants boost pyrrhotite-driven nitrogen removal in constructed wetlands - Cheng Shen; Liti Su; Yaqian Zhao; Wenbo Liu; Ranbin Liu; Fuhao Zhang; Yun Shi; Jie Wang; Qiuqi Tang; Yan Yang; Yu Bon Man; Jin Zhang (Bioresource Technology, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Expression and cellular localization of insulin-like growth factor 3 in gonads of the seasonal breeding teleost silver pomfret (Pampus argenteus) - Yaya Li; Yang Yang; Youyi Zhang; Jiabao Hu; Man Zhang; Jiachu Sun; Xinyue Tian; Yuxuan Jin; Dingyuan Zhang; Yajun Wang; Shanliang Xu; Xiaojun Yan (Fish Physiology and Biochemistry, 2022)

OsAPL controls the nutrient transport systems in the leaf of rice (Oryza sativa L.) - Zhen Yan; Man-Yu Yang; Biligen-Gaowa Zhao; Guo Li; Qing Chao; Feng Tian; Ge Gao; Bai-Chen Wang (Planta, 2022)

High-throughput “read-on-ski” automated imaging and label-free detection system for toxicity screening of compounds using personalised human kidney organoids - Qizheng Wang; Jun Lu; Ke Fan; Yiwei Xu; Yucui Xiong; Zhiyong Sun; Man Zhai; Zhizhong Zhang; Sheng Zhang; Yan Song; Jianzhong Luo; Mingliang You; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

White Matter “Matters” in Alzheimer’s Disease - Man-Yu Xu; Zhi-Qiang Xu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Predictive factors, preventive implications, and personalized surgical strategies for bone metastasis from lung cancer: population-based approach with a comprehensive cancer center-based study - Xianglin Hu; Wending Huang; Zhengwang Sun; Hui Ye; Kwong Man; Qifeng Wang; Yangbai Sun; Wangjun Yan (EPMA Journal, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

Hydraulic Performance of Self-priming Mesh Filter for Micro-irrigation in Northwest China - Zhenji Liu; Kai Shi; Yan Xie; Man Li (Agricultural Research, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Effects of Different Fertilizers on the Germination of Tomato and Cucumber Seeds - Min PAN; Pui Ching YAU; Kai Chun LEE; Hui Yan MAN (Water, Air, & Soil Pollution, 2022)

TUG1 knockdown suppresses cardiac fibrosis after myocardial infarction - Qingsong Sun; Man Luo; Zhiwei Gao; Xiang Han; Zhuan Yan; Shouxiang Xie; Hongmei Zhao; Hong Sun (Mammalian Genome, 2021)

The vascularization, innervation and myogenesis of early regenerated tail in Gekko japonicus - Zhuang Liu; Shuai Huang; Man Xu; Wenxue Zhang; Tuchen Guan; Qinghua Wang; Mei Liu; Jian Yao; Yan Liu (Journal of Molecular Histology, 2021)

Immune response of silver pomfret ( Pampus argenteus ) to Amyloodinium ocellatum infection - Youyi Zhang; Jiabao Hu; Yaya Li; Man Zhang; Kimran Jean Jacques; Weiwei Gu; Yibo Sun; Jiachu Sun; Yang Yang; Shanliang Xu; Yajun Wang; Xiaojun Yan (Journal of Fish Diseases, 2021)
Amyloodinium ocellatum (AO) infection in silver pomfret ( Pampus argenteus ) causes extensive mortality. Insufficient information exists on the molecular immune response of silver pomfret to AO infestation, so herein we simulated the process of silver pomfret being infected by AO. Translucent trophosomes were observed on the gills of AO‐infected fish. Transcriptome profiling was performed to investigate the effects of AO infection on the gill, kidney complex and spleen. Overall, 404,412,298 clean reads were obtained, assembling into 96,341 unigenes, which were annotated against public databases. In total, 2730 differentially expressed genes were detected, and few energy‐ and immune‐related genes were further assessed using RT‐qPCR. Moreover, activities of three immune‐related (SOD, AKP and ACP) and three energy‐related (PKM, LDH and GCK) enzymes were determined. AO infection activated the immune system and increased interleukin‐1 beta and immunoglobulin M heavy chain levels. Besides, the PPAR signalling pathway was highly enriched, which played a role in improving immunity and maintaining homeostasis. AO infection also caused dyspnoea, leading to extensive lactic acid accumulation, potentially contributing towards a strong immune response in the host. Our data improved our understanding regarding the immune response mechanisms through which fish coped with parasitic infections and may help prevent high fish mortality in aquaculture.

Influence of sedimentation rate on the environmental capacity of total nitrogen in the water of Bohai Bay, China - Yan Zhang; Anding Li; Ye Tian; Bin Zhou; Man Chai; Hui Li; Qiongqiong Liu; Hui Zeng; Weijie Xu (Journal of Soils and Sediments, 2021)

Dynamic process of rock avalanche and dynamic interaction between rock avalanche and hazard-bearing bodies - Zhong Fu Wang; Man He; Yan Wang; Jingzhuo Yang; Haoyuan Li (Arabian Journal of Geosciences, 2021)

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Heterologous expression and biochemical characterization of a cold-active lipase from Rhizopus microsporus suitable for oleate synthesis and bread making - Man Xiang; Ling Wang; Qiaojuan Yan; Zhengqiang Jiang; Shaoqing Yang (Biotechnology Letters, 2021)

Species and geographic specificity between endophytic fungi and host supported by parasitic Cynomorium songaricum and its host Nitraria tangutorum distributed in desert - Shuang-Man Miao; Yan-Yan Zhang; Jin-Long Cui; Gang Zhang (Archives of Microbiology, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Use of biochar as feed supplements for animal farming - Ka Yan Man; Ka Lai Chow; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

A high-density genetic map and multiple environmental tests reveal novel quantitative trait loci and candidate genes for fibre quality and yield in cotton - Qishen Gu; Huifeng Ke; Zhengwen Liu; Xing Lv; Zhengwen Sun; Man Zhang; Liting Chen; Jun Yang; Yan Zhang; Liqiang Wu; Zhikun Li; Jinhua Wu; et al. (Theoretical and Applied Genetics, 2020)

Inversion of time-domain airborne EM data with IP effect based on Pearson correlation constraints - Man Kai-Feng; Yin Chang-Chun; Liu Yun-He; Ren Xiu-Yan; Sun Si-Yuan; Miao Jia-Jia; Xiong Bin (Applied Geophysics, 2020)

Direct and indirect effects of microplastics on bivalves, with a focus on edible species: A mini-review - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ka Yan Man; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

The chemical constituents from the active fractions of Eleutherine bulbosa with their antimicrobial activity - Hai Jiang; Wen-Jing Man; A-Jiao Hou; Lin Yang; Xu-Dong Xing; Mei-Ling Yan; Xin-Yue Guo; Liu Yang (Natural Product Research, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

First report of actinidia virus A and B infecting kiwifruit in Jiangxi province in China - Man Fei Zou; Ming Feng Yan; Ying Zhou; Yuan Xiu Wang; Gui Hong Xiong; Jun Xi Jiang (Journal of Plant Pathology, 2020)

The Arabidopsis UDP-glycosyltransferase75B1, conjugates abscisic acid and affects plant response to abiotic stresses - Ting-Ting Chen; Fang-Fei Liu; Dong-Wang Xiao; Xiao-Yi Jiang; Pan Li; Shu-Man Zhao; Bing-kai Hou; Yan-jie Li (Plant Molecular Biology, 2020)

PGE2 facilitates tail regeneration via activation of Wnt signaling in Gekko japonicus - Man Xu; Tiantian Wang; Wenjuan Li; Yin Wang; Yanran Xu; Zuming Mao; Ronghua Wu; Mei Liu; Yan Liu (Journal of Molecular Histology, 2019)

Newly Developed Genomic SSRs Reveal Genetic Diversity in Wild and Cultivated Amorphophallus albus Germplasms - Si Yin; Yuehui Yan; Linguang You; Qiufen Chen; Yan Zhou; Kaiyang Chen; Ruidan Li; Zhiying Yang; Linqiong Man; Yong Gao (Plant Molecular Biology Reporter, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Design, synthesis, bioactivity, and DFT calculation of 2-thiazolyl-hydrazone derivatives as influenza neuraminidase inhibitors - Man-Ying Cui; Jian-Xia Nie; Zhong-Zhong Yan; Meng-Wu Xiao; Ding Lin; Jiao Ye; Ai-Xi Hu (Medicinal Chemistry Research, 2019)

Genome-Wide Classification and Evolutionary and Functional Analyses of the VQ Family - Hanyang Cai; Man Zhang; Yanhui Liu; Qing He; Mengnan Chai; Liping Liu; Fangqian Chen; Youmei Huang; Maokai Yan; Heming Zhao; Jerming Hu; Yuan Qin (Tropical Plant Biology, 2019)

Preemptive isolation and active surveillance in the prevention and control of nosocomial infection reduce the incidence of carbapenem-resistant Enterobacteriaceae - Qiqiang Liang; Chengmin Yan; Zhijiang Xu; Man Huang (Infectious Diseases, 2019)

Effect of long-distance inter-basin water transfer on the bioavailability of Cu for the receiving water - Yan Zhang; Lei Kang; Shiwei Geng; Jinmei Wang; Cuiling Tan; Xiaoqiao Wang; Weijie Xu; Man Chai (Environmental Science and Pollution Research, 2019)

Developing an electric vehicle urban driving cycle to study differences in energy consumption - Xuan Zhao; Jian Ma; Shu Wang; Yiming Ye; Yan Wu; Man Yu (Environmental Science and Pollution Research, 2019)

Three-component reaction of o-aminophenol (o-phenylenediamine), dialkyl acetylenedicarboxylate and 3-phenacylideneoxindolines - Man Xiao; Yan-Hong Jiang; Chao-Guo Yan (Molecular Diversity, 2019)

Modelling of turbulent dispersion for numerical simulation of wind-driven rain on bridges - Man Liu; Sheng Hong Huang; Bo Wen Yan; Qiu Sheng Li (Environmental Fluid Mechanics, 2018)

Optimization of Hydrolysis Conditions for the Isolation of Angiotensin-I Converting Enzyme (ACE) Inhibitory Peptides from Rhopilema hispidum - Zhenliang Sun; Huanlong Qin; Duo Cao; Xuebing Yan; Hao Li; Linsheng Huang; Xiao Qu; Cheng Kong; Man Wang (Journal of Ocean University of China, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Cellular stress and redox activity proteins are involved in gastric carcinogenesis associated with Helicobacter pylori infection expressing high levels of thioredoxin-1 - Yan-yan Shi; Jing Zhang; Ting Zhang; Man Zhou; Ye Wang; He-jun Zhang; Shi-gang Ding (Journal of Zhejiang University-SCIENCE B, 2018)

First report of leaf spot caused by Pseudocercospora puerariicola on kudzu (Pueraria lobata) in Jiangxi China - Ming Feng Yan; Man Fei Zou; Bing Liu; Yuan Xiu Wang; Gui Hong Xiong; Jun Xi Jiang (Journal of Plant Pathology, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Two new phenolic constituents from the root bark of Morus alba L. and their cardioprotective activity - Yan-gang Cao; Xiao-ke Zheng; Fang-fang Yang; Fang Li; Man Qi; Yan-li Zhang; Xuan Zhao; Hai-xue Kuang; Wei-sheng Feng (Natural Product Research, 2018)

PAX3 Promotes Cell Migration and CXCR4 Gene Expression in Neural Crest Cells - Man Xu; Yongle Li; Jinfeng Du; Hengrong Lin; Sixian Cao; Zuming Mao; Ronghua Wu; Mei Liu; Yan Liu; Qiyou Yin (Journal of Molecular Neuroscience, 2018)

Verrucosispora rhizosphaerae sp. nov., isolated from mangrove rhizosphere soil - Qing-yi Xie; Xiao-dong Bao; Qing-yu Ma; Fan-dong Kong; Man-li Zhou; Bing Yan; You-xing Zhao (Antonie van Leeuwenhoek, 2018)

Low Serum Levels of Brain-Derived Neurotrophic Factor Were Associated with Poor Short-Term Functional Outcome and Mortality in Acute Ischemic Stroke - Jing Wang; Li Gao; Yan-Long Yang; Yu-Qian Li; Tao Chang; Ming-Hao Man; Xing-Ye Zhang; Shao-Chun Guo; Li-Hong Li (Molecular Neurobiology, 2017)

Synthesis and evaluation of novel urea and amide derivatives of 2-amino-4-phenylthiazole as potential antibacterial agents - Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Yao Sun; Xiao-Man Yang; Xiao-Yu Cai; Song You (Medicinal Chemistry Research, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Two new sesquiterpene glycosides isolated from the fresh needles of Pinus massoniana Lamb. - Yun-Chuan Xiao; Liang Ye; Man-Xi Zhao; Cui-Qi Yan; Wei Wang; Quan-Shu Huang; Kai Liang; Bao-Hua Meng; Xiao Ke (Natural Product Research, 2017)

Numerical simulation on the effects of drug-eluting stents with different bending angles on hemodynamics and drug distribution - Yu Chen; Yan Xiong; Wentao Jiang; Man Sang Wong; Fei Yan; Qingyuan Wang; Yubo Fan (Medical & Biological Engineering & Computing, 2016)

‘One Health’ for the people of Hong Kong and the world - Kin-Hang Kok; Hei-Man Vincent Tang; Dong-Yan Jin (Science China Life Sciences, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Three-dimensional stability of landslides based on local safety factor - Tao Yang; Man-chu Ronald Yeung; Bing Yang; Yong-jiang Liu; Yan-xin Yang (Journal of Mountain Science, 2016)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

Involvement of polyphosphate kinase in virulence and stress tolerance of uropathogenic Proteus mirabilis - Liang Peng; Qiao Jiang; Jia-Yun Pan; Cong Deng; Jing-Yi Yu; Xiao-Man Wu; Sheng-He Huang; Xiao-Yan Deng (Medical Microbiology and Immunology, 2016)

Inorganic elemental determinations of marine traditional Chinese Medicine Meretricis concha from Jiaozhou Bay: The construction of inorganic elemental fingerprint based on chemometric analysis - Mingying Shao; Xuejie Li; Kang Zheng; Man Jiang; Cuiwei Yan; Yantuan Li (Journal of Ocean University of China, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Performance of ground penetrating radar in root detection and its application in root diameter estimation under controlled conditions - Shan Wing Yeung; Wai Man Yan; Chi Hang Billy Hau (Science China Earth Sciences, 2016)

Maturation of glutamatergic transmission in the vestibulo-olivary pathway impacts on the registration of head rotational signals in the brainstem of rats - Chun-Hong Lai; Chun-Wai Ma; Suk-King Lai; Lei Han; Hoi-Man Wong; Kelvin Wai-Kwok Yeung; Daisy Kwok-Yan Shum; Ying-Shing Chan (Brain Structure and Function, 2016)

Genetic architecture of maize kernel row number and whole genome prediction - Lei Liu; Yanfang Du; Dongao Huo; Man Wang; Xiaomeng Shen; Bing Yue; Fazhan Qiu; Yonglian Zheng; Jianbing Yan; Zuxin Zhang (Theoretical and Applied Genetics, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Expression of a scorpion toxin gene BmKit enhances the virulence of Lecanicillium lecanii against aphids - Ming Xie; Yan-Jun Zhang; Xiao-Man Zhai; Jin-Jin Zhao; De-Liang Peng; Gang Wu (Journal of Pest Science, 2015)

The associations between metals/metalloids concentrations in blood plasma of Hong Kong residents and their seafood diet, smoking habit, body mass index and age - Yan Yan Qin; Clement Kai Man Leung; Che Kit Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Projection of the Zhujiang (Pearl) River Delta’s potential submerged area due to sea level rise during the 21st century based on CMIP5 simulations - Jiangjiang Xia; Zhongwei Yan; Wen Zhou; Soi Kun Fong; Ka Cheng Leong; Iu Man Tang; S. W. Chang; W. K. Leong; Shaofei Jin (Acta Oceanologica Sinica, 2015)

Catalytic enhancement of the heme-based oxygen-sensing phosphodiesterase EcDOS by hydrogen sulfide is caused by changes in heme coordination structure - Fang Yan; Veronika Fojtikova; Petr Man; Martin Stranava; Markéta Martínková; Yongming Du; Dongyang Huang; Toru Shimizu (BioMetals, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

The Regenerating Spinal Cord of Gecko Maintains Unaltered Expression of β-Catenin Following Tail Amputation - Honghua Song; Lili Man; Yingjie Wang; Xue Bai; Sumei Wei; Yan Liu; Mei Liu; Xiaosong Gu; Yongjun Wang (Journal of Molecular Neuroscience, 2015)

Analysis of an antennal cDNA library and the expression patterns of two olfactory genes in Frankliniella occidentalis (Thysanoptera: Thripidae) - Fang-Fang Zeng; Shuang-Shuang Zhou; Yan-Hong Ding; Man-Qun Wang (Applied Entomology and Zoology, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Sex Differences in Iron Status and Hepcidin Expression in Rats - Wei-Na Kong; Qiao-Man Niu; Lan Ge; Nan Zhang; Shao-Feng Yan; Wei-Bin Chen; Yan-Zhong Chang; Shu-E Zhao (Biological Trace Element Research, 2014)

Calibration of the Normal Cutoff Values of Systolic Dyssynchrony of the Left Ventricular Synchronicity in Normal Subjects Using Real-Time 3-Dimensional Echocardiography and the Effects of Age and Heart Rate - Chun-Yan Ma; Shuang Liu; Qing Zhang; Jun Yang; Li Tang; Gabriel Yip; Cheuk-Man Yu (Cell Biochemistry and Biophysics, 2014)

Human health risk assessment based on trace metals in suspended air particulates, surface dust, and floor dust from e-waste recycling workshops in Hong Kong, China - Winifred Ka Yan Lau; Peng Liang; Yu Bon Man; Shan Shan Chung; Ming Hung Wong (Environmental Science and Pollution Research, 2014)

Passive Movement Improves the Learning and Memory Function of Rats with Cerebral Infarction by Inhibiting Neuron Cell Apoptosis - Man Li; Jun Peng; Meng-Die Wang; Yan-Ling Song; Yuan-Wu Mei; Yuan Fang (Molecular Neurobiology, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Erratum to: Conversion of a heme-based oxygen sensor to a heme oxygenase by hydrogen sulfide: effects of mutations in the heme distal side of a heme-based oxygen sensor phosphodiesterase (Ec DOS) - Yongming Du; Gefei Liu; Yinxia Yan; Dongyang Huang; Wenhong Luo; Marketa Martinkova; Petr Man; Toru Shimizu (BioMetals, 2013)

Conversion of a heme-based oxygen sensor to a heme oxygenase by hydrogen sulfide: effects of mutations in the heme distal side of a heme-based oxygen sensor phosphodiesterase (Ec DOS) - Yongming Du; Gefei Liu; Yinxia Yan; Dongyang Huang; Wenhong Luo; Marketa Martinkova; Petr Man; Toru Shimizu (BioMetals, 2013)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Activation of Akt and cardioprotection against reperfusion injury are maximal with only five minutes of sevoflurane postconditioning in isolated rat hearts - Yuan-yuan Yao; Man-hua Zhu; Feng-jiang Zhang; Chuan-yun Wen; Lei-lei Ma; Wen-na Wang; Can-can Wang; Xian-bao Liu; Li-na Yu; Ling-bo Qian; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Widespread expression of zinc transporter ZnT (SLC30) family members in mouse endocrine cells - Man-Li Zhong; Zhi-Hong Chi; Zhong-Yan Shan; Wei-Ping Teng; Zhan-You Wang (Histochemistry and Cell Biology, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Deterioration of Stress Distribution Due to Tunnel Creation in Single-Bundle and Double-Bundle Anterior Cruciate Ligament Reconstructions - Jie Yao; ChunYi Wen; Jason Tak-Man Cheung; Ming Zhang; Yong Hu; Chunhoi Yan; Kwong-Yuen Peter Chiu; William Weijia Lu; Yubo Fan (Annals of Biomedical Engineering, 2012)

High prevalence of Eimeria infection in dairy goats in Shaanxi province, northwestern China - Guang Hui Zhao; Li-Hui Lei; Chuan-Chuan Shang; Man Gao; Yan Qing Zhao; Chao-Xi Chen; De-Kun Chen (Tropical Animal Health and Production, 2012)

Chromium, Selenium, and Zinc Multimineral Enriched Yeast Supplementation Ameliorates Diabetes Symptom in Streptozocin-Induced Mice - Jun Liu; Wei Bao; Man Jiang; Yan Zhang; Xiping Zhang; Liegang Liu (Biological Trace Element Research, 2012)

Non-receptor tyrosine kinase 2 reaches its lowest expression levels in human breast cancer during regional nodal metastasis - Qing-Xiang Amy Sang; Yan-Gao Man; You Me Sung; Zahraa I. Khamis; Lihua Zhang; Mi-Hye Lee; Stephen W. Byers; Ziad J. Sahab (Clinical & Experimental Metastasis, 2012)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

A novel rice calmodulin-like gene, OsMSR2, enhances drought and salt tolerance and increases ABA sensitivity in Arabidopsis - Guo-Yun Xu; Pedro S. C. F. Rocha; Man-Ling Wang; Meng-Liang Xu; Yan-Chun Cui; Luo-Ye Li; Yu-Xing Zhu; Xinjie Xia (Planta, 2011)

Blocking gastrin and CCK-B autocrine loop affects cell proliferation and apoptosis in vitro - Jian Jiang Zhou; Man Ling Chen; Qun Zhou Zhang; Yan Zao; Yuan Xie (Molecular and Cellular Biochemistry, 2010)

Alteration in protein expression in estrogen receptor alpha-negative human breast cancer tissues indicates a malignant and metastatic phenotype - Ziad J. Sahab; Yan-Gao Man; Suzan M. Semaan; Robert G. Newcomer; Stephen W. Byers; Qing-Xiang Amy Sang (Clinical & Experimental Metastasis, 2010)

Persistent organic pollutants and heavy metals in adipose tissues of patients with uterine leiomyomas and the association of these pollutants with seafood diet, BMI, and age - Yan Yan Qin; Clement Kai Man Leung; Anna Oi Wah Leung; Sheng Chun Wu; Jin Shu Zheng; Ming Hung Wong (Environmental Science and Pollution Research, 2010)

Characterization of SARS-CoV-specific memory T cells from recovered individuals 4 years after infection - Yan-Ying Fan; Zi-Tong Huang; Li Li; Man-Hui Wu; Tao Yu; Richard A. Koup; Robert T. Bailer; Chang-You Wu (Archives of Virology, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

Presynaptic Ryanodine Receptor–CamKII Signaling is Required for Activity-dependent Capture of Transiting Vesicles - Man Yan Wong; Dinara Shakiryanova; Edwin S. Levitan (Journal of Molecular Neuroscience, 2009)

Cyclophosphamide promotes pulmonary metastasis on mouse lung adenocarcinoma - Shuli Man; Yanjun Zhang; Wenyuan Gao; Lulu Yan; Chaoyi Ma (Clinical & Experimental Metastasis, 2008)

Sources and seasonal variation of PAHs in the sediments of drinking water reservoirs in Hong Kong and the Dongjiang River (China) - Yan Liang; Pui Ka Fung; Man Fung Tse; Hua Chang Hong; Ming Hung Wong (Environmental Monitoring and Assessment, 2008)

Modulation of γ-aminobutyric acid on painful sense in central nervous system of morphine-dependent rats - Yan Xu; Man-Ying Xu; Xia Li (Neuroscience Bulletin, 2008)

Genetic relatedness and genetic diversity of ornamental mei (Prunus mume Sieb. et Zucc.) as analysed by AFLP markers - Chao-Dong Yang; Jun-Wei Zhang; Xiao-Lan Yan; Man-Zhu Bao (Tree Genetics & Genomes, 2008)

Genistein potentiates protein kinase A activity in porcine coronary artery - William W. H. Ng; Wendy Keung; Yan Chun Xu; Kwok F. J. Ng; George P. H. Leung; Paul M. Vanhoutte; Patrick C. Choy; Ricky Y. K. Man (Molecular and Cellular Biochemistry, 2008)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Studies on characteristics of nanostructure of N-TiO2 thin films and photo-bactericidal action - Ming-fang Xu; Shan Lin; Xin-man Chen; Yan-zhi Peng (Journal of Zhejiang University-SCIENCE B, 2006)

Study on spatial autocorrelation of urban land price distribution in Changzhou city of Jiangsu Province - Zhong-gang Liu; Man-chun Li; Yan Sun; Wen-bo Ma (Chinese Geographical Science, 2006)

The (GT)n polymorphism and haplotype of the COL1A2 gene, but not the (AAAG)n polymorphism of the PTHR1 gene, are associated with bone mineral density in Chinese - Shu-Feng Lei; Fei-Yan Deng; Volodymyr Dvornyk; Man-Yuan Liu; Su-Mei Xiao; De-Ke Jiang; Hong-Wen Deng (Human Genetics, 2005)

Two genes encoding protein phosphatase 2A catalytic subunits are differentially expressed in rice - Richard Man Kit Yu; Yan Zhou; Zeng-Fu Xu; Mee-Len Chye; Richard Yuen Chong Kong (Plant Molecular Biology, 2003)

The dynamic monitoring of horqin sand land using remote sensing - Yuan-man Hu; Yan Jiang; Yu Chang; Ren-cang Bu; Yue-hui Li; Chong-gang Xu (Chinese Geographical Science, 2002)

Sedimentary cycles of trace elements in Salawusu River Valley since 150 ka BP - Yao Chun-xial; Li Bao-sheng; Jin He-ling; David Dian Zhang; Yan Man-cun; Zhu Yi-zhi; Li Hou-xin; Zhang Yu-hong; Luo Kai-li (Journal of Geographical Sciences, 2002)

CaCO3 cycles in salawusu river basin since 150ka B.P. - Kai-li Luo; Bao-sheng Li; Yi-zhi Zhu; He-ling Jin; David Dian Zhang; Man-cun Yan; Hou-xin Li; Chun-xia Yao; Yu-hong Zhang (Chinese Geographical Science, 2001)

Hyperproduction of polyesters consisting of medium-chain-length hydroxyalkanoate monomers by strain Pseudomonas stutzeri 1317 - Jianzhong Xi; Qiong Wu; Yongbin Yan; Zengming Zhang; Peter H.F. Yu; Man-ken Cheung; Riqing Zhang; Guo-Qiang Chen (Antonie van Leeuwenhoek, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)